Effects of cyclosporine on ischemia-reperfusion injuries in rat kidneys. An experimental model - Oliveira, Antonio Carlos Cerqueira (2019)
Purpose: To assess Cyclosporine A (CsA) therapy at an intraperitoneal dose of 15 mg.kg-1 in a rodent model of non-septic renal ischemia. Methods: Twenty male Wistar rats were randomized to receive CsA therapy or none therapy before undergoing 30 minutes of renal ischemia followed by reperfusion. Additionally, 10 rats were randomized to undergo the same surgical procedure of the aforementioned animals with neither ischemia nor CsA therapy. Twelve hours after kidney ischemia, the left kidneys were evaluated for histological injury according to Park’s criteria. Serum creatinine (Cr), urea nitrogen (Ur) and sodium levels were obtained at different times of the experimental protocol. Results: Rodents in the CsA group showed negative results (p<0.05) in serum variables (Cr: 0.41±0.05mg/ dL vs. 4.17±1.25mg/dL; Ur: 40.90±3.98mg/dL vs. 187.70±22.93mg/dL) even the non CsA or control group (Cr: 0.35±0.07mg/dL vs. 3.80±1.20mg/dL; Ur: 40.10±4.70mg/dL vs. 184.50±49.80mg/dL). The negative results were also verified in histological evaluation, CsA group had 50% in the very severe grade of lesion, 10% in the severe and 40% in the moderate to severe whereas the control group had 90% in the very severe grade. Conclusion: CsA was incapable of preventing the deleterious effects of ischemia-reperfusion injury in rat kidneys.